Dos provimentos antecipatórios e o devido processo legal - Carvalho Júnior, Odilair (2007)
The goal of this work is to assess the compatibility of anticipatory provisions with the guarantee of due process of law. Starting from the observation of the possibility of collision between constitutional guarantees of principle, it verifies that the anticipatory provisions consolidate the given solution by the legislator upon the conflict between the guarantee of that which is contradictory and the guarantee of that which cannot be removed from jurisdictional control. It also seeks to encounter objective criteria in order to assess the validity of the legislator’s choice to make one constitutional principle prevail at the cost of restricting another. In order for this, the analysis of the historical evolution of fundamental rights and guarantees must be carried out. This work outlines the distinction between rights and guarantees. It studies the diverse functions resulting from the State’s sovereignty with emphasis on Jurisdiction. This paper analyzes the application of due process of law as the basis of criteria to be utilized for the solution of fortuitous conflict between the fundamental constitutional guarantees of that which is contradictory and Legal defense and that which cannot be removed from jurisdictional control. It seeks to delimit the range of due process of law in its two dimensions: procedural and substantive. This work shows the evolution of the guarantee of substantive due process of law starting from the proceedings of the United States Supreme Court. It gives the account of the application of substantive due process in Brazilian law. It demonstrates that the guarantee of due process of law is constituted in mechanism to be applied to the control of constitutionality of the prescriptive acts of Public Authority. It defines and delimits the range of concrete principles of due process of law: the principles of reasonability and of proportionality. It seeks to define the content of the guarantee of that which is contradictory and that which cannot be removed from jurisdictional control. This work groups together the kinds of jurisdictional provisions in guardianships of urgency and of proof. It compares these types of jurisdictional guardianships in light of criteria supplied through due process of law. It emphatically analyzes the preliminary verdict in possessory injunctions and in the proceedings of fiduciary alienation in guarantees.